(untitled) (Società e diritti, 2024)
The article focuses on the concepts of freedom in school and freedom of school and on the relationships between freedom of teaching and freedom of thought. The relationships between these freedoms are also examined in light of the main jurisprudence of the Italian Constitutional Court and the ECtHR